Innovative Approaches to Forming Management Competence of Future Officers At Higher Military Educational Institutions of Ukraine - Zabolotny, Serhii; Pavlenko, Oleh; Zabolotna, Olena; Potapchuk, Natalia; Kovalska, Iryna (Educological discourse, 2024)
The article analyses and summarises the experience of applying innovative approaches to the formation of managerial competence of future officers of communications units in the process of professional training in higher military education institutions in Ukraine. It is determined that the training methods and the technology for the formation of managerial competence of future officers of communications units are determined taking into account the functions of managerial activity of the officers of the specified units and the set of managerial qualities that need to be improved in order to form a complex of components of the managerial competence of a qualified head of a military unit. The authors characterised the peculiarities of the formation of management competence of future officers through the use in the educational process of higher military education institutions in Ukraine: professional (command and staff) games, training based on simulation modeling; information and communication technologies; training technologies and facilitation methods; problem-based learning and situational approach, which ensures the integrity, continuity and professional orientation of the educational process in higher military education institutions in Ukraine regarding the formation of managerial competence of future officers of communications units. It was found that the use of simulation modeling systems in the training of military specialists allows: to significantly reduce the cost of tactical, tactical-special and other exercises, which are carried out in a real dimension on training grounds; to diversify the possible scenarios of combat operations, which will allow to achieve a wide range of training goals and practice tactics and techniques of actions that are difficult to reproduce in a real environment and require certain auxiliary equipment, carry risks to environmental safety and the life and health of military personnel; to increase the level of tactical training of commanders of various ranks, which in the future can save the lives and health of servicemen during real combat operations. Keywords: managerial competence, approaches, future officers of communications units, professional training, higher military education institution.